Impact of National Training on Sorghum Cultivation for Value-addition - Rajendra R Chapke , VR Bhagwat and JV Patil, (Indian Journal of Extension Education, 2015)
The study was conducted at Directorate of Sorghum Research, Hyderabad on 20 trainees comprising of agricultureofficers from four state agricultural departments engaged in field extension to assess impact of the training programmeconducted on sorghum value-added products and sweet sorghum. The data were collected through direct interactions withthe participants and interview schedule . Results revealed that the learning index of the trainees was significantlycorrelated with their age, job experience, and level of satisfaction about training materials and atmosphere. Beforetraining, majority of them (60%) belonged to medium knowledge level (between 16 and 30 knowledge score) who hadmore than double knowledge score (49-84) after the training. Knowledge gained was found to be highly significant at0.001% level. The topics viz., improved package of practices for kharif and rabi sorghum cultivation followed byapproaches for transfer of improved sorghum technologies, sweet sorghum as versatile bio-energy crop, major weeds ofsorghum and their management and value-addition to sorghum with reference to its industrial uses and entrepreneurshipdevelopment were perceived as more useful. The overall impact on the trainees was found to be highly significant andencouraging. This course will help them in their job to organize effective extension programmes and encourage smallentrepreneurs at grass root level.